2017
DOI: 10.1038/nm.4367
|View full text |Cite
|
Sign up to set email alerts
|

Correction of a splicing defect in a mouse model of congenital muscular dystrophy type 1A using a homology-directed-repair-independent mechanism

Abstract: Splice-site defects account for about 10% of pathogenic mutations that cause Mendelian diseases. Prevalence is higher in neuromuscular disorders (NMDs), owing to the unusually large size and multi-exonic nature of genes encoding muscle structural proteins. Therapeutic genome editing to correct disease-causing splice-site mutations has been accomplished only through the homology-directed repair pathway, which is extremely inefficient in postmitotic tissues such as skeletal muscle. Here we describe a strategy us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 38 publications
0
57
0
1
Order By: Relevance
“…Here, we observed that rescue of a subset of nuclei was sufficient to yield partial rescue of myotonia. However, myotonia can be modeled as a loss-of-function event in which Clcn1 protein is lost, and there is evidence that in other recessive muscle diseases, gene editing of a small subset of nuclei can restore sufficient protein expression across muscle fibers to yield therapeutic benefit (Kemaladewi et al, 2017, Tabebordbar et al, 2016). Conversely, mis-splicing events yielding pathogenic isoforms with dominant-negative behavior may require full elimination to mitigate deleterious consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that rescue of a subset of nuclei was sufficient to yield partial rescue of myotonia. However, myotonia can be modeled as a loss-of-function event in which Clcn1 protein is lost, and there is evidence that in other recessive muscle diseases, gene editing of a small subset of nuclei can restore sufficient protein expression across muscle fibers to yield therapeutic benefit (Kemaladewi et al, 2017, Tabebordbar et al, 2016). Conversely, mis-splicing events yielding pathogenic isoforms with dominant-negative behavior may require full elimination to mitigate deleterious consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Immune response to Cas9 involving AAV-mediated, long-term expression in tissue is a major consideration for translation of any CRISPR-based therapeutic to the clinic. Recent efforts involving delivery of Cas9 to adult muscle have assessed immune response to varying degrees (27,28) and detailed assessments have revealed adaptive immune response to Cas9 (29). We assessed gene expression changes between RCas9-and Mbnltreated mice to assess the immune response to Cas9 protein and observed enrichment in adaptive immune response-linked genes ( Figure 3G) and no striking alterations in gene expression linked to innate immune response ( Figure S2).…”
Section: Main Textmentioning
confidence: 97%
“…We have previously demonstrated that an early intervention using CRISPR/Cas9-mediated correction of a splicing defect resulted in robust Lama2 restoration and prevention of disease manifestation 4 . Here we showed that upregulation of Lama1, when initiated at pre-disease-onset, leads to similar prevention.…”
Section: E)mentioning
confidence: 99%
“…23, 2018; Animal Use Protocol number 16-0234H. Intramuscular and temporal vein injections were preformed as previously described 4 . Systemic administration experiments were performed on 3-week-old dy 2j /dy 2j mice through tail vein injection.…”
Section: Animal Studies and Functional Testsmentioning
confidence: 99%
See 1 more Smart Citation